Does Knowledge Management Affect Competence and Workload in Nurses' Work Performance at Mitra Medika Pontianak Hospital - Budi Budi; Rina Anindita; Mus Aida (Jurnal Health Sains, 2022)
In the management of hospital management, it appears that there are problems in terms of nurses' work performance that is not optimal. This is thought to be influenced by various factors, including competence, workload, and knowledge management. So this study aims to describe, analyze, and determine the effect of competence, workload, and knowledge management on the performance of nurses at Mitra Medika Hospital Pontianak. This study analyzed the problem, using 148 respondents. The data collection technique used a survey method with a closed questionnaire. Data analysis was carried out by path analysis using SPSS software version 18.00. From the results of the study, it was found that the competence variable had an influence on work performance with a beta value of 0.316, a significance of 0.000; Workload has no effect on work performance with a beta value of 0.086, a significance of 0.86; Knowledge management has a significant effect on work performance with a beta value of 0.525, a significance of 0.000. Knowledge management is the variable with the most dominant influence on work performance.